A patient-centered view of symptoms, functional impact, and priorities in post-COVID-19 syndrome: cross-sectional results from the Québec Action Post-COVID cohort - Nancy E. Mayo; Marie-Josée Brouillette; Emilia Liana Falcone; Lesley K. Fellows (BMC Infectious Diseases)
Abstract Background Health services planning and mechanism-focused research would benefit from a clearer picture of symptoms, impact, and personal priorities in post-COVID-19 syndrome (PCS). This study aimed to provide estimates of the symptom, function, and quality of life (QOL) impact of PCS. Methods People living in Quebec, aged ≥ 18, were eligible for the Québec Action for/pour le Post-COVID (QAPC) study if they had symptoms lasting more than 4 weeks post-acute SARS-CoV-2 infection, with or without a positive COVID-19 test. Recruitment was through conventional and social media between September 2022 and December, 31, 2023. Standardized and individualized questionnaires, in French or English, were accessed through an online portal. We report cross-sectional results from the baseline visit. Results Individuals (n=535) spontaneously reported symptoms attributable to an average of 4.5 organ systems. Fatigue was most frequent. Effects on function and quality of life were moderate to severe and had already persisted for a year or more in the majority. Personal intervention priorities included fatigue and post-exercise malaise (PEM), cognitive symptoms, shortness of breath, and impaired taste and smell. Except for PEM, women and men did not differ importantly on measures of PCS impact, while older age was associated with lower impact. Conclusion Symptom clusters defined a range of severity, with fatigue a pervasive symptom at all levels of severity. Participants in this study are likely to be representative of those seeking health care for post-COVID-19 symptoms in Canada and the results can inform next steps for clinical, research, and health services planning.